2020
DOI: 10.1088/1755-1315/421/6/062018
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of flax husk production technology as raw material for cellulose nanomaterials

Abstract: Experimental studies on ultrasonic dispersion of the organic complex of flax stem in the voiced medium on the installation of continuous operation IUSD-01 were carried out, flax fiber with high quality indicators was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
“…by height, it is necessary to take into account the geometric features of the production facility. It is advisable to introduce into formula (23) a coefficient that takes into account how many times the height of the production facility is less than its length, d, m: 𝑘 г • .…”
Section: Mathematics and Methodsmentioning
confidence: 99%
“…The most important organic compounds are shives, by weight. %: cellulose up to 77.4; hemicellulose up to 16.2; soluble substances up to 3.4; resins, fats, wax up to 1.9 [11,12]. From which it follows that due to the large amount of cellulose and hemicellulose, as well as the content of natural organic adhesives, shives can be used for the production of universal biodegradable packaging for food and industrial goods.…”
Section: Introductionmentioning
confidence: 99%